Electronically Tunable Transparent Conductive Thin Films for Scalable Integration of 2D Materials with Passive 2D–3D Interfaces. (22nd January 2022) - Grünleitner, Theresa; Henning, Alex; Bissolo, Michele; Kleibert, Armin; Vaz, Carlos A.F.; Stier, Andreas V.; Finley, Jonathan J.; Sharp, Ian D.
Abstract: A novel transparent conductive support structure for scalable integration of 2D materials is demonstrated, providing an electronically passive 2D–3D interface while also enabling facile interfacial charge transport. This structure, which comprises an evaporated nanocrystalline carbon (nc‐C) film beneath nanometer‐thin atomic layer deposited AlOx, is thermally stable and allows direct chemical vapor deposition of 2D materials onto the surface. The combination of spatial uniformity, enhanced charge screening, and low interface defect concentrations yields a tenfold enhancement of MoS2 photoluminescence intensity compared to flakes on conventional Si/SiO2, while also retaining the strong optical contrast for monolayer flakes. Tunneling across the ultrathin AlOx enables facile interfacial charge injection, which is utilized for high‐resolution scanning electron microscopy and photoemission electron microscopy with no detectable charging. Thus, this combination of scalable fabrication and electronic conductivity across a weakly interacting 2D–3D interface opens up new opportunities for device integration and characterization of 2D materials. Abstract : The novel transparent conductive support structure provides an electronically passive 2D–3D interface that maintains a good optical contrast of the underlying material while also enabling facile interfacial charge transport. The scalable integration of 2D materials results in a tenfold photoluminescence enhancement compared to MoS2 on a standard Si/SiO2 substrate.